2019 IEEE Intl Conf on Dependable, Autonomic and Secure Computing, Intl Conf on Pervasive Intelligence and Computing, Intl Conf 2019
DOI: 10.1109/dasc/picom/cbdcom/cyberscitech.2019.00188
|View full text |Cite
|
Sign up to set email alerts
|

Gold Price Forecast Based on LSTM-CNN Model

Abstract: An accurate prediction is certainly significant in financial data analysis. Investors have used a series of econometric techniques on pricing, stock selection and risk management but few of them have found great success due to the fact that most of them only are purely based on a single scheme. Recent advances in deep learning methods have also demonstrated the outstanding performance in the fields of image recognition and sentiment analysis. In this paper, we originally propose a novel gold price forecast met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…In studies conducted by Siami-Namini et al (2018), LSTM-based algorithms show significant improvement in the accuracy of future prediction as compared to ARIMA. He et al, (2019) supported this in their finding where LSTM-based models performed significantly better than ARIMA in forecasting precious metal prices. Wu et al, (2018) proposed LSTM forecasting framework in the forecast of Bitcoin volatility concluded that values projected by LSTM are nearer to the actual values on a non-stationary time series data.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In studies conducted by Siami-Namini et al (2018), LSTM-based algorithms show significant improvement in the accuracy of future prediction as compared to ARIMA. He et al, (2019) supported this in their finding where LSTM-based models performed significantly better than ARIMA in forecasting precious metal prices. Wu et al, (2018) proposed LSTM forecasting framework in the forecast of Bitcoin volatility concluded that values projected by LSTM are nearer to the actual values on a non-stationary time series data.…”
Section: Introductionmentioning
confidence: 71%
“…While the forecasting of gold bullion price is a well-researched area (Alameer et al, 2019;Hadavandi et al, 2010;He et al, 2019;Livieris et al, 2020;Pandey et al, 2019;Ping et al, 2013;Vidal & Kristjanpoller, 2020;Zhang & Liao, 2014), studies that specifically predicts the Kijang Emas gold coin price remains limited. Miswan et al, (2013) used the Box-Jenkins methodology to develop an ARIMA-based model to predict the Kijang Emas value while Ping et al, (2013) produced a GARCH model which can provide a better prediction than the ARIMA-based models.…”
Section: Introductionmentioning
confidence: 99%
“…ARIMA, RF, and XGBoost were executed without any further configurations. [15] This approach first uses the LSTM model, followed by CNN for parameter classification. Initially, this model was used to predict gold prices.…”
Section: Baselinesmentioning
confidence: 99%
“…It should be noted that CNN methods can handle inherent data complexities, e.g., spatio-temporality, chaotic nature, and non-stationarity, only in cases when they are designed and/or evaluated for each specific dataset and application. To let CNNs work, they need to be initialized with a large number of labels [47].…”
Section: Compressed Sensing-convolutional Neural Network: the Proposmentioning
confidence: 99%